2014
DOI: 10.1016/j.eplepsyres.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Rufinamide as an adjunctive therapy for Lennox–Gastaut syndrome: A randomized double-blind placebo-controlled trial in Japan

Abstract: The present results showed a favorable risk-benefit profile for rufinamide as an adjunctive therapy for patients with LGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 27 publications
0
37
0
8
Order By: Relevance
“…Все побочные эффекты были легкими или умеренными по степени тяжести. Таким образом, по мнению авторов исследования, руфинамид проде-монстрировал благоприятное соотношение польза-риск в дополнительной терапии пациентов с СЛГ [28].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Все побочные эффекты были легкими или умеренными по степени тяжести. Таким образом, по мнению авторов исследования, руфинамид проде-монстрировал благоприятное соотношение польза-риск в дополнительной терапии пациентов с СЛГ [28].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…29 Similarly, in a double-blind Japanese study of children and adults with LGS, body weight and age were not found to affect the circulating rufinamide concentration. 40 Rufinamide clearance appears to be 6%-14% lower in females than in males. 29 Race and renal function also do not seem to affect the pharmacokinetics of rufinamide; 31 however, the drug is not recommended for patients with severe hepatic impairment.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Clinical global impressions of the patients' conditions were significantly better in the rufinamide group than in the placebo group (P=0.007). 40 …”
Section: Rufinamide In Patients With Lgsmentioning
confidence: 99%
See 2 more Smart Citations